Underwriter price support and the IPO underpricing puzzle - Ruud, Judith S (Journal of Financial Economics, 1993)
This paper reassesses the apparent systematic underpricing of initial public offerings (IPOs). Investigation of the distribution of initial returns following IPOs shows that positive mean initial returns may reflect the existence of a partially unobserved left (negative) tail. Moreover, most IPOs with zero one-day returns subsequently fall in price, suggesting that underwriter price support may account for the skewed distribution and hence the phenomenon of positive average initial IPO returns, even if offering prices are set at expected market value. This paper thus challenges the presumption underlying previous research that positive average initial IPO returns result primarily from deliberate underpricing.